El clima organizacional y su influencia en la satisfacción laboral de los trabajadores de la unidad educativa particular futuros navegantes de la ciudad de Guayaquil - Miño Ruales, Claudia Lilia (2016)
The organizational climate is important for the development of workers within a company, especially if it is an educational institution as is the case of Private Education Unit "Future Navigators", where it is believed that staff at a stage where the organizational climate has the best conditions for development and which other problems such as delays arising in the process and that there are unexpected resignations that affect the organization and performance with students. The overall objective of this research is to analyze the relationship between organizational climate and job satisfaction of workers in the Special Education Unit "Future Navigators" of the city of Guayaquil and its specific objectives is to diagnose job satisfaction workers of this entity…….